The impact of Low Emission Zones on particulate matter concentration and public health: A Comment. (December 2015) - Morfeld, Peter; Groneberg, David A.; Spallek, Michael
Highlights: Low Emission Zones (LEZs) are introduced in many European cities. LEZ effects on air pollution are small and bias control is of paramount importance. PM10 level reductions were ⩽ 0.2 μg/m 3 (⩽1%) in our study. This is considerably smaller than estimated byMalina and Scheffler (2015) . Monetary health benefits estimates are probably too high inMalina and Scheffler (2015) . Abstract: Malina and Scheffler estimated the impact of Low Emission Zones (LEZs). LEZ effects are small and bias control is of paramount importance. Based on our analyses we conclude that the point estimate of monetary health benefits calculated by Malina and Scheffler is probably too high and the uncertainty reported possibly too small.